Réponses

  • Utilisateur Brainly
2014-09-03T13:25:42+02:00
A= 1 + 5/3 * (-2/7)
A= 1 - (2 * 5)/(7 * 3)
A= 1 - 10/21
A= 21/21 - 10/21
A= 11/21

B= 5/3 * 3/2 - 3
B= (3 * 5)/(2 * 3) - 3
B= 15/6 - 18/6
B= - 3/6
B= - 1/2

C= (5/3 - 2/7)(- 2/7 - 3/2)
C= [(5 * 7)/(3 * 7) - (2 * 3)/(7 * 3)][- (2 * 2)/(7 * 2) - (3 * 7)/(2 * 7)]
C= (35/21 - 6/21)(- 4/14 - 21/14)
C= 29/21 * (- 25/14)
C= - (29 * 25)/(21 * 14)
C= - 725/294
2014-09-03T13:48:55+02:00
A = 1 + xy
A = 1 + 5/3 x - 2/7
A = 1 + (- 10/21)
A = 1 - 10/21
A = 1 x 21 / 1 x 21 - 10/21
A = 21/21 - 10/21
A = 11/21

B = x - 3
B = 5/3 x 3/2 - 3
B = 15/6 - 3
B = 15/6 - 3 x 6 / 1 x 6
B = 15/6 - 18/6
B = - 3/6
B = 3 x - 1 / 3 x 2
B = - 1/2

C = (x + y) (y - z)
C = (5/3 - 2/7) (- 2/7 - 3/2)
C = ( 5 x 7 / 3 x 7 - 2 x 3 / 7 x 3)  (- 2 x 2 / 7 x 2 - 3 x 7 / 2 x 7)
C = (35/21 - 6/21)  (- 4/14 - 21/14)
C = 29/21 * - 25/14
C = 725 /- 294
C = - 725/294